Place rootedness suggesting the loss and survival of historical public spaces - Harun, Nor Zalina; Mansor, Mazlina; Said, Ismail (Elsevier Ltd., 2015)
Place meaning was created by people throughout their gradual experience of the place. Some will have deep and meaningful while some are pale and meaningless. Place meaning has an intertwined relationship with place attachment, where both involve diverse and distinct physical properties and social attributes. This study aims to decode place rootedness as a salient dimension in the theory of place attachment. It seeks to search for a meaning of historical public space in two historical cities in Malaysia. Two historical public spaces with different fate and state are chosen as case study area. Seventy five residents were interviewed on their perceptual responses toward the survival of Padang Kota Lama and the loss of Padang Pahlawan. Results show that both groups discuss the sense of rootedness toward the public space in a very positive term. They evaluate its distinct characteristics in term of long engagement, historical events, and place for social interaction and important moment they had during childhood days. A persistent and deeply-felt concern expressed by all participants of Padang Pahlawan is their regret that it could not enjoyed and preserved as it should be. The finding from the survey also reveals that sense of rootedness is highly conceded with the sense of pride and fear of losing the historical public space which is developed through its high historical values and uniqueness. The study concludes that both public spaces constitute an important aspect of residents’ place identity and belongingness, which enable them to simultaneously remain connected to it.